The marsh and the bush : outlaw hero traditions of China and the West. - Zhang, Ye (Curtin University, 1998)
This thesis makes a comparative study of cultural differences and similarities between Chinese and Western outlaw heroes. It examines this cultural phenomenon from eight angles: the outlaw hero as constructed by history, literature and folklore; outlaws constructed as archetypal heroes; social and cultural contexts; outlaw heroes and revolution; a comparative case study of outlaws in Northeast China and Australia; underground cultural products (the "lore" and 'law"); ballads and proverbs reflecting values of outlaw heroism; and the fate of outlaws and the outlaw hero.Historical and folkloric explanatory frameworks are applied to outlaw hero traditions. Archetypal outlaw heroes and their successors, praised or criticised, are all constructed through a long process which combines reality recreated and fiction made real. Characteristics of archetypal outlaw heroes are inherited by later outlaws in China and the West. Though there are common codes and values of outlaw heroes in China and the West, different attributes are manifested in their attitudes towards brotherhood, organisation and women, and also in bandit sources and bandit categories.Western outlaw heroes are seldom involved in revolution, but their Chinese counterparts are connected with the Taiping revolutionary movement, the republican revolution and the Communist revolution. Some Communists are no more than outlaw heroes in the eyes of the poor and bandits in the eyes of the Kuomintang However, the alliance between outlaw heroes and revolutionaries is a fragile one.Northeast China and Australia have some parallels in their outlaw hero traditions. Convicts and immigrants play an important part in frontier banditry. The environment of both provides fertile soil for banditry and immigration. Among modem outlaws in Northeast China are chivalrous bandits and bandits who heroically fight against foreign Invaders. Bandit culture is valuable heritage in China. Bandits' ceremonies, argot, internal regulations, worship and superstition, and routine and recreational activities are all important facets of Chinese outlaw culture.Outlaw heroes never bend their bodies under pressure; they rebel rather than wait for death; and they never rob the locals. This is all reflected in bandit ballads, proverbs and other lore discussed in the thesis. Death is what most outlaws have to face, and how to fade it is a significant element in the construction of the outlaw hero. The arguments of this thesis are based on folkloric, historic and literary sources, many of which are here translated into English for the first time.